An exploratory analysis of spirituality and spiritual intelligence among selected administrators of small private secondary schools in Region IV - Borromeo, Roberto T. (2003)
Recent studies on spirituality in the workplace underscore the positive impact of spirituality on the organization and its employees. While numerous books and articles have been written on the topic, there is still no consensual definition of spirituality. This paper analyzed how spirituality is defined and manifested by selected administrators of private secondary schools in Region IV, using the Psycho-matrix Spiritual Inventory developed by Wolman (2001). The results showed that the respondents generally had a high level of spiritual intelligence except in the areas of Mindfulness and Intellectuality.
Keywords: Spirituality; Employee motivation